2019
DOI: 10.33594/000000119
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile of the Bradycardic Agent Ivabradine on Human Cardiac Ion Channels

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
5
23
0
Order By: Relevance
“…Similarly it increased action potential duration in an isolated rabbit heart by 16% (at 5 µM), while lower concentrations were ineffective [ 46 ] and increased APD in fetal mouse hearts [ 43 ]. The fact that in all these studies resting membrane potential was unchanged despite prolongation of APD further corroborates that this effect was mediated by I Kr inhibition [ 41 , 42 , 43 ]. Studies indicate that ivabradine at 10 μM blocks approximately 20–60% of I Kr [ 47 ] and 80% of HCN4 current [ 43 ].…”
Section: Effect Of Ivabradine On Ion Channelssupporting
confidence: 64%
See 2 more Smart Citations
“…Similarly it increased action potential duration in an isolated rabbit heart by 16% (at 5 µM), while lower concentrations were ineffective [ 46 ] and increased APD in fetal mouse hearts [ 43 ]. The fact that in all these studies resting membrane potential was unchanged despite prolongation of APD further corroborates that this effect was mediated by I Kr inhibition [ 41 , 42 , 43 ]. Studies indicate that ivabradine at 10 μM blocks approximately 20–60% of I Kr [ 47 ] and 80% of HCN4 current [ 43 ].…”
Section: Effect Of Ivabradine On Ion Channelssupporting
confidence: 64%
“…Delpon et al found that the hKv1.5 was blocked by the drug in a concentration-dependent way with IC 50 29.0 ± 1.9 μM, therefore at doses higher than those required to block HCN channels [ 40 ]. Moreover, in the clinically relevant doses ivabradine did not affect calcium channels [ 41 ] and inhibited sodium channels at high concentrations (IC 50 30 ± 3 μM) [ 6 , 41 ].…”
Section: Effect Of Ivabradine On Ion Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of I Na may contribute to antiarrhythmic but not APD-prolonging effect. In previous studies, ivabradine showed no effect or prolonging or shortening effect on APD in wild type cells (Table 1) (Koncz et al, 2011;Haechl et al, 2019). It seems that ivabradine effect on APD mainly resulted from its effect on I Kr .…”
Section: Discussionmentioning
confidence: 79%
“…Besides hERG current, I Na , but not I Ca-L , I Ks and I K1 can be inhibited by ivabradine (Supplementary Table 1) (Haechl et al, 2019;Demontis et al, 2009). The inhibition of I Na may contribute to antiarrhythmic but not APD-prolonging effect.…”
Section: Discussionmentioning
confidence: 99%